2000
DOI: 10.1094/pdis.2000.84.3.341
|View full text |Cite
|
Sign up to set email alerts
|

Rice Pest Constraints in Tropical Asia: Characterization of Injury Profiles in Relation to Production Situations

Abstract: A protocol for characterizing patterns of rice cropping practices and injuries due to pathogens, insects, and weeds was developed and used in six sites in tropical Asia covering a wide range of environments where lowland rice is cultivated. The data collected in a total population of 456 individual farmers' fields were combined to site-specific weather data and analyzed using non-parametric multivariate techniques: cluster analyses with chi-square distance and correspondence analyses. The main results are: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 12 publications
1
59
0
1
Order By: Relevance
“…The same has been reported by Shabana et al (2008) for fungicides and anti-oxidants against brown leaf spot. Similarly, the results of this study have also been supported by the findings of Savary et al (2000) who reported that brown leaf spot caused yield loss up to 5% along with qualitative loss and can be managed by the use of fungicides. Various fungicides were also found effective for controlling diseases as reported by Moletti et al (1996); Cortesi et al (2003); Mandal et al (2008) and Mia et al (2001).…”
Section: Resultssupporting
confidence: 88%
“…The same has been reported by Shabana et al (2008) for fungicides and anti-oxidants against brown leaf spot. Similarly, the results of this study have also been supported by the findings of Savary et al (2000) who reported that brown leaf spot caused yield loss up to 5% along with qualitative loss and can be managed by the use of fungicides. Various fungicides were also found effective for controlling diseases as reported by Moletti et al (1996); Cortesi et al (2003); Mandal et al (2008) and Mia et al (2001).…”
Section: Resultssupporting
confidence: 88%
“…In 1942, an epidemic of the disease was one of the major factors contributing to the great Bengal famine, which reportedly claimed the lives of no less than 2 million Indians (Stuthman, 2002). Nowadays, brown spot is as prev-alent as ever, with recent studies by Savary et al (2000aSavary et al ( , 2000b showing that among the many diseases occurring in rice fields, brown spot, along with sheath blight (Rhizoctonia solani), accounts for the highest yield loss across all production situations in south and southeast Asia. Although the genetic and molecular bases of the rice-C. miyabeanus interaction are still poorly understood, it is known that, like other Cochliobolus species, the fungus employs a varied arsenal of phytotoxins to trigger host cell death (Xiao et al, 1991).…”
mentioning
confidence: 99%
“…and Jain (teleomorph=Cochliobolus miyabeanus) is an important disease of rice throughout the world (Ou, 1985;Savary et al, 2000a), and is responsible for the reduction of 26 to 52 per cent gain in yield (Chakrabarti, 2001). The disease is known to occur in resource poor farmers' fields where there is deficiency of water supply and nitrogenous fertilizers (Zadoks, 1974).…”
Section: Introductionmentioning
confidence: 99%